Pengaruh Beban Kerja dan Self Control terhadap Cyberloafing Melalui Motivasi Kerja sebagai Variabel Intervening pada UPT Puskesmas Talang Kabupaten Solok - Shelvina Meiliza Pramesti,; Yamasitha Yamasitha,; Chintya Ones Charli, (Journal of Management and Creative Business, 2025)
This research aims to determine the effect of workload and self control on cyberloafing through work motivation as an intervention variable at the Talang Community Health Center UPT, Solok Regency. The data collection method is through surveys and distributing questionnaires to employees as respondents using a quantitative approach. The data analysis technique used is structural analysis Equation Modeling (SEM) with Partial Least Square (PLS) 3.0.The results of the research show that there is a positive and significant influence between workload and cyberloafing at the Talang Community Health Center UPT, Solok Regency. There is a positive and significant influence between workload and work motivation at the Talang Community Health Center UPT, Solok Regency. There is a positive and significant influence between work motivation and cyberloafing at the Talang Community Health Center UPT, Solok Regency. There is a negative and insignificant influence between self control and cyberloafing at the Talang Community Health Center UPT, Solok Regency. There is a positive and significant influence between self control and work motivation at the Talang Community Health Center UPT, Solok Regency. There is a positive and significant influence between workload on cyberloafing through work motivation as an intervention variable at the Talang Community Health Center UPT, Solok Regency. There is a positive and significant influence between self control on cyberloafing through work motivation as an intervention variable at the Talang Community Health Center UPT, Solok Regency.